KOLABORASI LINTAS AKTOR SEBAGAI STRATEGI MENGURAI KETERBATASAN KAPASITAS PELAYANAN KESEJAHTERAAN SOSIAL - Muhammad Fatchul Annaji (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2026)
Abstract. The structural capacity limitations of local governments in providing social welfare services trigger the urgency to involve Social Welfare Institutions (LKS); however, the high disparity in LKS' institutional readiness cannot be equitably accommodated. Amidst this gap, the Social Welfare Coordinating Agency (BK3S) emerges as a strategic bridge. This study aims to analyze the impact of collaboration and the significance of Collaborative Governance among the social services department, BK3S, and LKS in strengthening social welfare services. Employing an exploratory qualitative method with a case study approach, this study proves that Collaborative Governance effectively breaks down the structural exclusivity of bureaucracy that limits the government's scope of action, forcing it to collaborate adaptively. The main finding asserts that the presence of a non-governmental actor, namely BK3S, plays a crucial role as an intermediary institution in bridging the government's capacity deficit through the strengthening of institutional governance and human resources within LKS. The practical implication of this research emphasizes the need for cross-actor synergy in social policy, while theoretically enriching the Collaborative Governance literature in the context of resource-constrained governance. Keyword: Collaborative Governance; Non-Governmental Organizations; Services; Social Welfare; BK3S. Abstrak. Keterbatasan kapasitas struktural pemerintah daerah dalam pelayanan kesejahteraan sosial memicu urgensi pelibatan Lembaga Kesejahteraan Sosial (LKS), namun tingginya disparitas kesiapan kelembagaan LKS tidak dapat diakomodir secara merata. Ditengah kesenjangan ini, hadir Badan Koordinasi Kegiatan Kesejahteraan Sosial (BK3S) sebagai jembatan strategis. Penelitian ini bertujuan menganalisis dampak kerja sama dan letak penting Collaborative Governance antara Dinas Sosial DIY, BK3S, dan LKS terhadap penguatan layanan kesejahteraan sosial. Menggunakan metode kualitatif eksploratif dengan pendekatan studi kasus, penelitian ini membuktikan bahwa Collaborative Governance secara efektif mendobrak eksklusivitas struktural birokrasi yang membatasi ruang gerak pemerintah dan memaksanya untuk berkolaborasi secara adaptif. Temuan utama menegaskan bahwa kehadiran aktor non-pemerintah yaitu BK3S berperan krusial sebagai lembaga intermediari dalam menjembatani defisit kapasitas pemerintah melalui penguatan tata kelola kelembagaan dan sumber daya manusia pada LKS. Implikasi praktis penelitian ini menekankan perlunya sinergi lintas aktor dalam kebijakan sosial, sementara secara teoretis memperkaya literatur Collaborative Governance pada konteks penyelenggaraan pemerintahan dengan sumber daya terbatas. Kata Kunci: Tata Kelola Kolaboratif; Organisasi Nonpemerintah; Pelayanan; Kesejahteraan Sosial; BK3S.